DEVELOPMENT AND VALIDATION OF A 24-HOUR DIETARY RECALL FOR ASSESSING EATING HABITS (REMUNOM, 2026)
Introduction: Accurate assessment of dietary intake is fundamental to public health but faces challenges, especially in populations with memory or cognitive limitations. Visual and simplified instruments can improve data accuracy. Objective: The primary objective of this study was to develop and validate a simple, illustrated 24-hour food recall (24HR) to quantify the dietary habits of children and adolescents. Secondarily, it aimed to discuss the potential application of this instrument for the adult population. Methods: The sample consisted of 113 participants aged 7 to 16 years. The instrument, which uses images and simple language, was subjected to construct validity (principal component analysis), internal consistency (Cronbach's alpha), and reproducibility (intraclass correlation coefficient - ICC) analyses. Results: The internal consistency analysis showed a Cronbach's alpha value of 0.81, indicating good reliability. The principal component analysis extracted a single factor that explained 73.57% of the total variance, with all variables showing adequate saturation (≥ 0.70). The ICC for total macronutrient intake was 0.661 (95% CI: 0.45-0.81), demonstrating good reproducibility. Conclusion: The illustrated 24HR showed robust evidence of validity and reproducibility for assessing the dietary habits of children and adolescents. Additionally, its intrinsic characteristics—such as the use of images and simplicity—suggest a promising potential for its secondary application in adult populations, especially those with lower literacy levels or cognitive difficulties, representing a versatile tool for nutritional epidemiology.